2021
DOI: 10.1002/jnr.24985
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning the role of inwardly rectifying potassium (Kir) channel in epilepsy

Abstract: Epilepsy is a neurological disease characterized by two spontaneous seizures occurring within 24 hr, or two spontaneous seizures within 10 years after an unprovoked seizure (Fisher et al., 2014). The disease occurs by an increased tendency to generate seizures attributed to abnormal brain activity, caused by the disruption of the dynamic excitatory and inhibitory neuronal balance in the central nervous system (CNS) (Navidhamidi et al., 2017). Aberrant connectivity between neuronal networks may result in pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 283 publications
(344 reference statements)
0
8
0
Order By: Relevance
“…to the relationships between Kir4.1 dysfunction and various diseases, including depression, epilepsy, and multiple sclerosis (Akyuz et al, 2022;Brickshawana et al, 2014;Cui et al, 2018;Kinboshi et al, 2020;Xiong et al, 2019). The present findings regarding the role of Kir4.1 in orofacial allodynia suggest that Kir4.1 may be also considered as a therapeutic target for neuropathic pain.…”
Section: Conditional Knockdown Of Kir41 Evoked Mechanical Allodynia I...mentioning
confidence: 54%
See 2 more Smart Citations
“…to the relationships between Kir4.1 dysfunction and various diseases, including depression, epilepsy, and multiple sclerosis (Akyuz et al, 2022;Brickshawana et al, 2014;Cui et al, 2018;Kinboshi et al, 2020;Xiong et al, 2019). The present findings regarding the role of Kir4.1 in orofacial allodynia suggest that Kir4.1 may be also considered as a therapeutic target for neuropathic pain.…”
Section: Conditional Knockdown Of Kir41 Evoked Mechanical Allodynia I...mentioning
confidence: 54%
“…Similarly, a previous study reported that silencing Kir4.1 in the TG via direct injection of long double‐stranded RNA induced orofacial pain‐like behaviors in rats (Vit et al, 2008). In recent years, increasing attention has been paid to the relationships between Kir4.1 dysfunction and various diseases, including depression, epilepsy, and multiple sclerosis (Akyuz et al, 2022; Brickshawana et al, 2014; Cui et al, 2018; Kinboshi et al, 2020; Xiong et al, 2019). The present findings regarding the role of Kir4.1 in orofacial allodynia suggest that Kir4.1 may be also considered as a therapeutic target for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of hyperpolarization-activated cation current I h were evident in both naïve- and CCI-PVIN recordings ( Table 4 ). The voltage-gated subthreshold currents, including M-type potassium current I M (Shah et al, 2008), the persistent sodium current I NaP (Vervaeke et al, 2006), and the inward rectifier potassium current I Kir (Akyuz et al, 2022), has been associated with generating mAHP and spike frequency adaptation. Despite the fact that these currents also modulate the passive membrane properties, which remain unaffected following nerve injury, their contribution to the PVINs excitability remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a chronic, severe, and devastating neurological condition characterized by repeated intermittent seizures that affect over 65 million people worldwide [ 1 , 2 ]. Focal seizures occur more frequently in both adults and children compared to generalized seizures.…”
Section: Introductionmentioning
confidence: 99%